Pengaruh Tekanan Dan Peluang Terhadap Deteksi Fraud Pada Bank BUMN Kota Batam - Desi Setia Nengsih; Andi Auliya Ramadhany; Nur Isra Laili; Maya Richmayati; Khadijah (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2026)
This study aims to examine the effect of pressure (X1) and opportunity (X2) on fraud detection ability (Y) in State-Owned Banks in Batam City. This research used a quantitative method by collecting primary data through questionnaires distributed to 189 respondents working as tellers and customer service staff at State-Owned Banks (Bank Negara Indonesia, Bank Rakyat Indonesia, and Bank Tabungan Negara). Data analysis was conducted using multiple linear regression with SPSS version 25. The results showed that partially, pressure (X1) had a significant negative effect on fraud detection ability (Y) with a significance value of 0.000, and opportunity (X2) also had a significant negative effect with a significance value of 0.000. Simultaneously, pressure and opportunity had a significant effect on fraud detection ability with a significance value of 0.000. Classical assumption tests indicated no autocorrelation, multicollinearity, or heteroscedasticity, and the data were normally distributed. This study suggests that State-Owned Banks should manage work pressure effectively and minimize fraud opportunities to improve fraud detection ability.